Efektivitas Metode Pemberian Tugas LKS Terhadap Hasil Belajar Siswa Kelas VII SMP Al-Hasan Banyuning Laok Geger - Erwin Baharuddin; Hefi Rusnita Dewi; M. Sahid (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
This research is a quantitative descriptive study conducted at Al-Hasany Middle School on Grade VII students with 13 students, consisting of 7 men and 5 women to determine student learning outcomes and responses, initial steps taken to help provide questions and make points -the main points of discussion will be used as learning tools consisting of lesson plans, worksheets and the necessary research instruments consisting of worksheet questions. After this research is conducted, the results of the evaluation of student activities are obtained, evaluation data on the implementation of lesson plans, learning outcome data and student response data. the implementation of the introductory lesson plan one produced a presentation of 82.5% with a very good category, and observer two produced a presentation of 75% with a very good category. And can be used to finish late lesson plans about Civics learning using discussion methods that are implemented very well. Student activities during learning, the discussion went well, in category, very good, with a scale of 78.75 this means that student activities included in active activities and learning methods of giving LKS assignments run effectively and well. Of the 13 students who did not complete as many as 4 while the total score of 9 students. From completeness students learn to complete if the number of students who complete reaches a percentage of ≥85%. In other words learning using the LKS task assistance method in class VII Al-Hasany Middle School in this study was asked to be effective because the number of students who completed reached a percentage of 69.23%.